Pouch film laminate and battery case manufactured using the same

The pouch film laminate with specific thickness and strength properties addresses cracking issues in battery cases by ensuring high rigidity and resistance to external stress, enabling larger electrode assemblies and reduced damage.

JP2025501547APending Publication Date: 2025-01-22LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024537148
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-24
Filing Date
2022-12-23
Publication Date
2025-01-22

AI Technical Summary

Technical Problem

Existing pouch-type battery cases face issues with cracking due to external stress when increased molding depth is required for larger electrode assemblies, leading to reduced rigidity and potential damage during logistics and charging/discharging processes.

Method used

A pouch film laminate with a gas barrier layer thickness of 60 μm or more, a base layer with tensile strength of 10 kgf/15 mm to 20 kgf/15 mm, and an elongation rate of 150% to 235% in the TD direction, combined with a sealant layer, enhances rigidity and resistance to external stress.

Benefits of technology

The laminate provides excellent moldability and resistance to external stress, allowing for a larger housing space and high energy density while minimizing damage from external impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501547000001_ABST
    Figure 2025501547000001_ABST
Patent Text Reader

Abstract

The present invention relates to a pouch film laminate that can be used to manufacture a high-strength battery case that has excellent resistance to external stress, and a battery case manufactured using the same. The pouch film laminate of the present invention includes a gas barrier layer having a thickness of 60 μm or more, a base layer that is disposed on one side of the gas barrier layer and has a tensile strength in the TD direction of 10 kgf / 15 mm to 20 kgf / 15 mm and an elongation in the TD direction of 150% to 235%, and a sealant layer that is disposed on the other side of the gas barrier layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0187273 filed on December 24, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a pouch film laminate and a battery case manufactured using the same, and more particularly, to a pouch film laminate that can manufacture a high-strength battery case with less cracking due to external stress, and a battery case manufactured using the same. [Background technology]

[0003] Secondary batteries are used not only in small products such as digital cameras, P-DVDs, MP3Ps, mobile phones, PDAs, portable game devices, power tools, and E-bikes, but also in large products that require high output such as electric cars and hybrid cars, as well as in power storage devices and backup power storage devices that store surplus generated electricity and new renewable energy.

[0004] Generally, a secondary battery is manufactured by coating a positive electrode current collector and a negative electrode current collector with an electrode active material slurry to manufacture a positive electrode and a negative electrode, laminating them on both sides of a separator to form an electrode assembly of a predetermined shape, housing the electrode assembly in a battery case, injecting an electrolyte, and sealing the case.

[0005] Secondary batteries are divided into pouch type and can type depending on the material of the case that houses the electrode assembly. The pouch type houses the electrode assembly in a pouch made of a flexible polymer material, while the can type houses the electrode assembly in a case made of metal or plastic.

[0006] The pouch-type battery case is manufactured by pressing a flexible pouch film laminate to form a cup portion, and then, after the cup portion is formed, an electrode assembly is placed in the receiving space of the cup portion and the seal portion is sealed to manufacture a secondary battery.

[0007] Among such press processes, drawing is performed by inserting a pouch film into a press device and applying pressure to the pouch film laminate with a punch to stretch the pouch film laminate. The pouch film laminate is generally formed of multiple layers, with a polymer film such as polyethylene terephthalate laminated on one side of a gas barrier layer made of a metal material and a sealant layer laminated on the other side.

[0008] Recently, as the demand for high-capacity batteries such as electric vehicle batteries and ESS batteries increases, the demand for battery cases capable of accommodating more electrode assemblies is also increasing. Accordingly, attempts have been made to increase the molding depth of the cup part of a pouch-type battery case, or to form cup parts in the upper and lower cases to increase the volume of the cup parts by using a two-cup molding method. However, when increasing the molding depth of the cup part or performing two-cup molding, excessive elongation occurs, reducing the rigidity of the battery case, which can lead to cracks caused by stress generated during logistics management or externally.

[0009] Therefore, there is a need to develop a pouch-type battery case having a large volume of a cup portion and high rigidity so that the storage volume of the electrode assembly can be increased. Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made to solve the above problems, and aims to provide a pouch film laminate and a battery case manufactured using the same, in which the thickness of the gas barrier layer and the tensile strength and elongation rate of the base material layer are controlled within specific ranges to increase the molding depth of the cup portion or to have excellent rigidity even after performing two-cup molding. [Means for solving the problem]

[0011] In one aspect, the present invention provides a pouch film laminate including: a gas barrier layer having a thickness of 60 μm or more; a base layer disposed on one surface of the gas barrier layer, the base layer having a tensile strength in the TD direction of 10 kgf / 15 mm to 20 kgf / 15 mm and an elongation in the TD direction of 150% to 235%; and a sealant layer disposed on the other surface of the gas barrier layer.

[0012] The pouch film laminate according to the present invention can be subjected to repeated application of force at loads of 100N and 150N to a sample produced by molding the pouch film laminate into two cups with a molding depth of 9.6 mm, and then cutting the sample into a size of 15 mm x 80 mm, and the number of times that force can be applied until breakage occurs can be 2000 or more.

[0013] In addition, in the pouch film laminate according to the present invention, when a sample prepared by cutting the pouch film laminate into a size of 90 mm x 100 mm is repeatedly pierced with a pin having a diameter of 1.0 mm at a load of 20 N, the number of times that force is applied until a hole is made can be 250 or more.

[0014] In addition, in the pouch film laminate according to the present invention, when a sample prepared by cutting the pouch film laminate into a size of 90 mm x 100 mm is repeatedly pierced with a pin having a diameter of 1.0 mm at a load of 22 N, the number of times that force is applied until a hole is made can be 150 or more.

[0015] The gas barrier layer may have a thickness of 60 μm to 80 μm.

[0016] Preferably, the base layer may have a tensile strength in the TD direction of 10 kgf / 15 mm to 18 kgf / 15 mm, and an elongation in the TD direction of 170% to 235%.

[0017] The base layer may have a laminated structure of a polyethylene terephthalate film and a nylon film, in which the polyethylene terephthalate film has a thickness of 5 μm to 20 μm, and the nylon film has a thickness of 20 μm to 30 μm.

[0018] The gas barrier layer may include an aluminum alloy thin film, and the aluminum alloy thin film may contain 1.2 wt % to 1.7 wt % of iron and have a crystal grain size of 10 μm to 13 μm.

[0019] The sealant layer may have a thickness of 60 μm to 100 μm and may include unstretched polypropylene, acid-modified polypropylene, polypropylene-butylene-ethylene copolymer, or a combination thereof.

[0020] In another aspect, the present invention provides a battery case manufactured by drawing the above-mentioned pouch film laminate according to the present invention. Effect of the Invention

[0021] The pouch film laminate according to the present invention, which employs a gas barrier layer having a thickness of 60 μm or more and a base layer having a tensile strength in the TD direction of 10 kgf / 15 mm to 20 kgf / 15 mm and an elongation in the TD direction of 150% to 235%, not only has excellent formability but also has strong resistance to external stress even after forming.

[0022] Specifically, the pouch film laminate of the present invention is molded into two cups to a molding depth of 9.6 mm, and then cut to a size of 15 mm x 80 mm to produce a sample. When a force of 100 N and 150 N is repeatedly applied to the sample until breakage occurs, the number of times that a force is applied until breakage occurs is 2000 or more. When a sample of the pouch film laminate is cut to a size of 90 mm x 100 mm to produce a sample, the number of times that a force is applied until a hole is created is 250 or more with a pin having a diameter of 20 N, and when a load of 22 N is repeatedly pierced, the number of times that a force is applied until a hole is created is 150 or more. Thus, the resistance to external stress is excellent.

[0023] Therefore, by using the pouch film laminate of the present invention, a battery case can be manufactured that has a large storage space for an electrode assembly, realizes high energy density, and minimizes damage caused by external stress that occurs during logistics and charging / discharging processes. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a cross-sectional view of a pouch film laminate according to one embodiment of the present invention. [Diagram 2] 1 is a diagram illustrating a battery case according to an embodiment of the present invention. [Diagram 3] 13A and 13B are diagrams illustrating a battery case according to another embodiment of the present invention. [Figure 4] 1 is a photograph showing a device for measuring the tensile strength of a base material layer. [Diagram 5] 1 is a photograph showing a pouch film laminate formed in two cups during a fatigue test of the pouch film laminate and the cutting positions of the samples. [Figure 6] 1 is a photograph showing a puncture cycle test apparatus for pouch film laminates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will now be described in more detail.

[0026] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0027] In the present invention, the MD direction (machine direction) means the longitudinal direction of the pouch film laminate, and the TD direction (transverse direction) means the width direction of the pouch film laminate.

[0028] The present inventors have conducted extensive research to manufacture a battery case that has a large storage space for a battery assembly, can realize a high energy density, and can suppress the occurrence of cracks due to external stress generated during logistics and charging / discharging processes. As a result, they have found that the above-mentioned objects can be achieved by adjusting the thickness of the gas barrier layer and the tensile strength and elongation in the TD direction of the base layer of the pouch film laminate within specific ranges, and have thus completed the present invention.

[0029] <Pouch film laminate> FIG. 1 illustrates one embodiment of a pouch film laminate according to the present invention. Hereinafter, the pouch film laminate according to the present invention will be described with reference to FIG.

[0030] 1, a pouch film laminate 1 according to the present invention includes a gas barrier layer 20, a base layer 10 disposed on one side of the gas barrier layer, and a sealant layer 30 disposed on the other side of the gas barrier layer. Here, the gas barrier layer 20 has a thickness of 60 μm or more, preferably 60 μm to 100 μm, and the base layer 10 has a tensile strength in the TD direction of 10 kgf / 15 mm to 20 kgf / 15 mm, preferably 10 kgf / 15 mm to 18 kgf / 15 mm, more preferably 10 kgf / 15 mm to 15 kgf / 15 mm, and even more preferably 10 kgf / 15 mm to 13 kgf / 15 mm, and an elongation in the TD direction of 150% to 235%, preferably 170% to 235%, and even more preferably 200% to 235%. Research by the present inventors has shown that when the thickness of the gas barrier layer 20 and the tensile strength and elongation in the TD direction of the base layer 10 simultaneously fall within the above ranges, the moldability is excellent and the resistance to external stress after molding is significantly increased. In contrast, when either the thickness of the gas barrier layer or the tensile strength of the base layer deviates from the range of the present invention, the resistance to external stress after molding is significantly decreased.

[0031] Specifically, the pouch film laminate of the present invention is molded into two cups so that the depth of the cup portion is 9.6 mm, and then cut to a size of 15 mm x 80 mm to produce a sample. When a load of 100 N (low force) and 150 N (high force) is repeatedly applied to the sample, the number of times that a force is applied until breakage occurs is 2000 or more, preferably 2000 to 10,000.

[0032] Here, the sample is cut so as to include the cup portion, and cut so that the TD direction of the pouch film laminate coincides with the longitudinal direction of the sample.

[0033] In addition, the two-cup molding is performed by inserting the pouch film laminate into a two-cup molding device and applying pressure to a partial region of the pouch film laminate with a punch to form a cup portion, thereby manufacturing the battery case 100. Here, the pressure may be about 0.3 MPa to 1 MPa, preferably 0.3 MPa to 0.8 MPa, and more preferably 0.4 MPa to 0.6 MPa. If the pressure during molding of the cup portion is too low, excessive squeezing may occur, resulting in wrinkles, and if the pressure is too high, squeezing may not be performed well, resulting in a reduced molding depth.

[0034] Meanwhile, the moving speed of the punch may be 20 mm / min to 80 mm / min, preferably 30 mm / min to 70 mm / min, more preferably 40 mm / min to 60 mm / min. If the moving speed of the punch is too fast, the peripheral surface of the cup part is not sufficiently stretched and a compressive force acts on the peripheral surface, which may cause wrinkles due to buckling. If the moving speed of the punch is too slow, the stress concentrated on the corners of the cup part during molding may increase, which may cause pinholes and cracks to occur.

[0035] Meanwhile, the die conditions of the two-cup molding apparatus used in the present invention are as shown in the following [Table 1].

[0036] [Table 1]

[0037] In addition, the pouch film laminate of the present invention has a size of 90 mm x 100 mm, and when a sample is repeatedly pierced with a 1.0 mm diameter pin at a load of 20 N, the number of times a force is applied until a hole is made is 250 or more, and when a load of 22 N is repeatedly pierced, the number of times a force is applied until a hole is made is 150 or more. Thus, even when a force is repeatedly applied from the outside, the pouch film laminate of the present invention is easily broken or does not make a hole, and maintains high rigidity even after molding. Therefore, when a battery case is manufactured using the pouch film laminate of the present invention, it is possible to effectively prevent the battery case from being damaged or broken by an external impact.

[0038] Each layer of the pouch film laminate according to the present invention will now be described in detail.

[0039] Base material layer The substrate layer 10 is disposed on the outermost layer of the battery case to protect the electrode assembly from external impacts and to provide electrical insulation.

[0040] The substrate layer 10 may be made of a polymer material, for example, one or more polymer materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, polyparaphenylene benzobisoxazole, polyarylate, and Teflon (registered trademark).

[0041] The substrate layer 10 may have a single layer structure, or may have a multi-layer structure in which different polymer films 12 and 14 are laminated as shown in Fig. 1. When the substrate layer 10 has a multi-layer structure, an adhesive layer 16a may be interposed between the polymer films.

[0042] Meanwhile, the substrate layer 10 may have a total thickness of 10 μm to 60 μm, preferably 20 μm to 50 μm, and more preferably 30 μm to 50 μm. When the substrate layer has a multi-layer structure, the thickness includes the thickness of the adhesive layer. When the substrate layer 10 satisfies the above range, it has excellent durability, insulation, and formability. If the substrate layer is too thin, the durability decreases and the substrate layer may be damaged during the forming process, and if the substrate layer is too thick, the formability may decrease, the total thickness of the pouch film laminate film may increase, the battery storage space may decrease, and the energy density may decrease.

[0043] In the present invention, the base layer may have a tensile strength in the TD direction of about 10kgf / 15mm to 20kgf / 15mm, more preferably 10kgf / 15mm to 18kgf / 15mm, more preferably 10kgf / 15mm to 15kgf / 15mm, and even more preferably 10kgf / 15mm to 13kgf / 15mm. If the tensile strength in the TD direction of the base layer is less than 10kgf / 15mm, there is little improvement in fatigue and puncture resistance after cup molding. On the other hand, if the tensile strength in the TD direction of the base layer is too high, the moldability may decrease, so the tensile strength in the TD direction of the base layer is preferably 20kgf / 15mm or less.

[0044] Meanwhile, the tensile strength of the substrate layer is the strength at which breakage occurs when the substrate layer is pulled in the TD direction, and can be measured by cutting a film or film laminate constituting the substrate layer so that the TD direction is the longitudinal direction to prepare a measurement sample, and then mounting the measurement sample in a UTM device and pulling it to measure the maximum strength at which breakage occurs.

[0045] The base layer may have an elongation percentage in the TD direction of about 150% to 235%, preferably 170% to 235%, more preferably 200% to 235%, and even more preferably 210% to 235%. When the elongation percentage in the TD direction of the base layer satisfies the above range, the gas barrier layer is well fixed and the effect of improving formability can be obtained.

[0046] The tensile strength and elongation rate in the TD direction of the base layer are affected by the material of the film constituting the base layer, the manufacturing method of the film, the thickness of the film, the thickness of the adhesive layer, etc. In addition, since the film manufacturing process differs for each manufacturer, even if the film is of the same material and thickness, if the manufacturer is different, the physical properties such as tensile strength and elongation rate may differ. Therefore, by appropriately selecting the manufacturer (manufacturing company) of the film constituting the base layer, the material of the film, the thickness of the film, the thickness of the adhesive layer, etc., a base layer having the desired tensile strength and elongation rate can be formed.

[0047] According to one embodiment, the base layer 10 may have a structure in which a polyethylene terephthalate (PET) film and a nylon film are laminated with an adhesive layer interposed therebetween. Here, it is preferable that the nylon film is disposed on the gas barrier layer 20 side, i.e., on the inside, and the polyethylene terephthalate film is disposed on the surface side of the battery case.

[0048] Polyethylene terephthalate (PET) has excellent durability and electrical insulation, and when a PET film is placed on the surface side, it has excellent durability and insulation. However, in the case of a PET film, the adhesion to the aluminum alloy thin film constituting the gas barrier layer 20 is weak, and the stretching behavior is also different, so when a PET film is placed on the gas barrier layer side, peeling between the base layer and the gas barrier layer may occur during the molding process, and the gas barrier layer may not be stretched uniformly, resulting in a problem of reduced moldability. In contrast, since the stretching behavior of a nylon film is similar to that of the aluminum alloy thin film constituting the gas barrier layer 20, when a nylon film is placed between the polyethylene terephthalate and the gas barrier layer, it is possible to obtain an effect of improving moldability.

[0049] The polyethylene terephthalate film may have a thickness of 5 μm to 20 μm, preferably 5 μm to 15 μm, and more preferably 7 μm to 15 μm, and the nylon film may have a thickness of 20 μm to 40 μm, preferably 20 μm to 35 μm, more preferably 20 μm to 30 μm, and more preferably 23 μm to 27 μm. When the thicknesses of the polyethylene terephthalate film and the nylon film satisfy the above ranges, the moldability and rigidity after molding are excellent.

[0050] Gas Barrier Layer The gas barrier layer 20 is intended to ensure the mechanical strength of the battery case, to block the entry and exit of gas or moisture from the outside of the secondary battery, and to prevent electrolyte leakage.

[0051] The gas barrier layer may have a thickness of 60 μm or more, preferably 60 μm to 100 μm, and more preferably 60 μm to 80 μm. When the gas barrier layer has a thickness of 60 μm or more, moldability is improved, the limit molding depth is increased, and resistance to external stress after molding is improved.

[0052] Meanwhile, the gas barrier layer may be made of a metal material, specifically, an aluminum alloy thin film.

[0053] The aluminum alloy thin film may contain aluminum and one or more metal elements other than aluminum, such as iron (Fe), copper (Cu), chromium (Cr), manganese (Mn), nickel (Ni), magnesium (Mg), silicon (Si), and zinc (Zn).

[0054] Preferably, the aluminum alloy thin film has an iron (Fe) content of 1.2wt% to 1.7wt%, preferably 1.3wt% to 1.7wt%, more preferably 1.3wt% to 1.45wt%. If the iron (Fe) content in the aluminum alloy thin film is less than 1.2wt%, the strength of the aluminum alloy thin film is reduced, and cracks and pinholes may occur during forming, and if it exceeds 1.7wt%, the flexibility of the aluminum alloy thin film is reduced, and there is a limit to the improvement of formability and bendability.

[0055] The aluminum alloy thin film includes an aluminum alloy thin film having a crystal grain size of 10 μm to 13 μm, preferably 10.5 μm to 12.5 μm, and more preferably 11 μm to 12 μm. When the crystal grain size of the aluminum alloy thin film satisfies the above range, the forming depth can be increased without the occurrence of pinholes or cracks during cup forming. When the crystal grain size of the aluminum alloy thin film exceeds 13 μm, the strength of the aluminum alloy thin film decreases and the occurrence of cracks and pinholes increases due to the difficulty in dispersing internal stress during stretching, while when the crystal grain size is less than 10 μm, the flexibility of the aluminum alloy thin film decreases, limiting the improvement of formability and bendability.

[0056] The grain size varies depending on the composition of the aluminum alloy thin film and the processing method of the aluminum alloy thin film, and can be measured by observing a cross section of the aluminum alloy thin film in the thickness direction with a scanning electron microscope (SEM). Specifically, in the present invention, a cross section SEM image of the aluminum alloy thin film in the thickness direction is obtained using a scanning electron microscope, and the maximum diameters of any 30 crystal grains among the crystal grains observed in the SEM image are measured, and the average value of these is evaluated as the grain size.

[0057] Specifically, the aluminum alloy thin film may be an aluminum alloy having alloy number AA8021, but is not limited thereto.

[0058] Sealant Layer The sealant layer 30 is bonded by thermocompression to seal the battery case, and is located as the innermost layer of the pouch film laminate 1.

[0059] The sealant layer 30 is the surface that comes into contact with the electrolyte and the electrode assembly after being molded into a battery case, and therefore must have insulating properties and corrosion resistance. It must also have high sealing properties since it must completely seal the inside and prevent material transfer between the inside and the outside.

[0060] The sealant layer 30 may be made of a polymer material, for example, one or more selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, polyparaphenylene benzobisoxazole, polyarylate, and Teflon (registered trademark). Among them, it is particularly preferable to include polypropylene (PP), which has excellent mechanical properties such as tensile strength, rigidity, surface hardness, abrasion resistance, and heat resistance, and chemical properties such as corrosion resistance.

[0061] More specifically, the sealant layer 30 may include polypropylene, cast polypropylene (CPP), acid modified polypropylene, polypropylene-butylene-ethylene copolymer, or a combination thereof.

[0062] The sealant layer 30 may have a single layer structure or a multi-layer structure including two or more layers made of different polymer materials.

[0063] The sealant layer may have a total thickness of 60 μm to 100 μm, preferably 60 μm to 90 μm, and more preferably 60 μm to 80 μm. If the thickness of the sealant layer is too thin, the seal durability and insulation properties may decrease, and if the thickness is too thick, the flexibility may decrease, the total thickness of the pouch film laminate may increase, and the energy density relative to the volume may decrease.

[0064] The pouch film laminate of the present invention as described above may be manufactured by a method for manufacturing a pouch film laminate well known in the art. For example, the pouch film laminate of the present invention may be manufactured by a method in which a base layer 10 is attached to an upper surface of a gas barrier layer 20 by an adhesive, and a sealant layer 30 is formed on a lower surface of the gas barrier layer 20 by coextrusion or an adhesive layer, but is not limited thereto.

[0065] The pouch film laminate according to the present invention may have a total thickness of 160 μm to 200 μm, preferably 180 μm to 200 μm. When the thickness of the pouch film laminate satisfies the above range, it is possible to minimize the reduction in battery accommodating space and the deterioration of sealing durability due to the increase in the thickness of the pouch laminate, and to increase the molding depth.

[0066] <Battery case> Next, the battery case according to the present invention will be described.

[0067] An embodiment of a battery case according to the present invention is illustrated in Figures 2 and 3. Hereinafter, the battery case according to the present invention will be described with reference to Figures 2 and 3.

[0068] As shown in Figs. 2 and 3, the battery case 100 according to the present invention is manufactured by drawing the above-mentioned pouch film laminate 1 according to the present invention, and includes at least one cup portion 110a, 110b.

[0069] The pouch film laminate 1 is as described above, and a detailed description thereof will be omitted.

[0070] The cup portions 110a and 110b are spaces 112 for accommodating an electrode assembly (not shown) and an electrolyte (not shown), and are manufactured by drawing the pouch film laminate 1 using a punch or the like. Here, the drawing can be performed by pressing a punch against the sealant layer side of the pouch film laminate 1.

[0071] Meanwhile, the battery case 100 according to the present invention may include one cup portion 110a as shown in FIG. 2, or may include two cup portions 110a and 110b as shown in FIG.

[0072] Meanwhile, the battery case 100 according to the present invention includes a lower case 110 and an upper case 120, and the cup parts 110a and 110b may be formed in only one or both of the lower case 110 and the upper case 120. When the pouch film laminate 1 is molded using a one-cup molding device, a battery case having one cup part can be manufactured as shown in Fig. 2, and when the pouch film laminate 1 is molded using a two-cup molding device, a battery case having cup parts formed in both the lower case 110 and the upper case 120 can be manufactured as shown in Fig. 3.

[0073] After the electrode assembly is accommodated in the cup parts 110a and 110b and an electrolyte is injected, the upper case 120 is folded to contact the upper end of the lower case 110, thereby isolating the electrode assembly and the electrolyte from the outside.

[0074] Thereafter, the corners of the upper case 120 and the lower case 110 are heat-pressurized to perform a sealing process.

[0075] The battery case of the present invention manufactured as described above has a large storage space for the electrode assembly, thereby realizing high energy density and minimizing damage caused by external stress occurring during logistics and charging / discharging processes.

[0076] The present invention will now be described in more detail with reference to specific examples.

[0077] Example 1 A 25 μm-thick nylon film (product name: Nylon 6, manufactured by: Toray) and a 12 μm-thick polyethylene terephthalate (PET) film (manufactured by: Toray) were laminated on one side of an 80 μm-thick AA8021 aluminum (Al) alloy thin film (manufactured by: SAMA Aluminum) by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer was 5 μm thick. Next, molten acid-modified polypropylene (PPa) and polypropylene (PP) were co-extruded on the other side of the aluminum alloy thin film to a thickness of 30 μm each to form a 60 μm-thick sealant layer, thereby manufacturing a pouch film laminate.

[0078] Example 2 A nylon film (trade name: Nylon6, manufactured by: HYOSUNG) having a thickness of 25 μm and a polyethylene terephthalate (PET) film (manufactured by: HYOSUNG) having a thickness of 12 μm were laminated on one side of an AA8021 aluminum (Al) alloy thin film (manufactured by: SAMA Aluminum) having a thickness of 80 μm by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer had a thickness of 3 μm. Next, molten polypropylene (PP) was extruded on the other side of the aluminum alloy thin film to a thickness of 30 μm, and a 30 μm-thick non-oriented polypropylene film (CPP) was attached thereto to form a sealant layer having a thickness of 60 μm, thereby manufacturing a pouch film laminate.

[0079] Example 3 A 25 μm-thick nylon film (product name: Nylon 6, manufactured by: Toray) and a 12 μm-thick polyethylene terephthalate (PET) film (manufactured by: Toray) were laminated on one side of a 60 μm-thick AA8021 aluminum (Al) alloy thin film (manufactured by: SAMA Aluminum) by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer was 5 μm thick. Next, molten acid-modified polypropylene (PPa) and polypropylene (PP) were co-extruded on the other side of the aluminum alloy thin film to a thickness of 40 μm each to form a sealant layer with a thickness of 80 μm, thereby manufacturing a pouch film laminate.

[0080] Example 4 A 25 μm-thick nylon film (product name: Nylon 6, manufacturer: HYOSUNG) and a 12 μm-thick polyethylene terephthalate (PET) film (manufacturer: HYOSUNG) were laminated on one side of a 60 μm-thick AA8021 aluminum (Al) alloy thin film (manufacturer: SAMA Aluminum) by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer had a thickness of 3 μm. Next, molten polypropylene (PP) was extruded on the other side of the aluminum alloy thin film to a thickness of 30 μm, and a 30 μm-thick non-oriented polypropylene film (CPP) was attached to form a 60 μm-thick sealant layer to manufacture a pouch film laminate.

[0081] Comparative Example 1 A 15 μm-thick nylon film (product name: Nylon 6, manufacturer: HYOSUNG) and a 12 μm-thick polyethylene terephthalate (PET) film (manufacturer: HYOSUNG) were laminated on one side of a 40 μm-thick AA8021 aluminum (Al) alloy thin film (manufacturer: SAMA Aluminum) by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer was 5 μm thick. Next, molten acid-modified polypropylene (PPa) and polypropylene (PP) were co-extruded on the other side of the aluminum alloy thin film to a thickness of 40 μm each to form a sealant layer with a thickness of 80 μm, thereby manufacturing a pouch film laminate.

[0082] Comparative Example 2 A 15 μm-thick nylon film (product name: Nylon 6, manufacturer: HYOSUNG) and a 12 μm-thick polyethylene terephthalate (PET) film (manufacturer: HYOSUNG) were laminated on one side of a 60 μm-thick AA8021 aluminum (Al) alloy thin film (manufacturer: SAMA Aluminum) by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer was 5 μm thick. Next, molten acid-modified polypropylene (PPa) and polypropylene (PP) were co-extruded on the other side of the aluminum alloy thin film to a thickness of 40 μm each to form an 80 μm-thick sealant layer, thereby manufacturing a pouch film laminate.

[0083] Comparative Example 3 A 25 μm-thick nylon film (product name: Nylon 6, manufactured by: Toray) and a 12 μm-thick polyethylene terephthalate (PET) film (manufactured by: Toray) were laminated on one side of a 40 μm-thick AA8021 aluminum (Al) alloy thin film (manufactured by: SAMA Aluminum) by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer had a thickness of 5 μm. Next, molten acid-modified polypropylene (PPa) and polypropylene (PP) were co-extruded on the other side of the aluminum alloy thin film to a thickness of 40 μm each to form a sealant layer with a thickness of 80 μm, thereby manufacturing a pouch film laminate.

[0084] Comparative Example 4 A nylon film (trade name: Nylon 6, manufactured by: KOLON) having a thickness of 25 μm and a polyethylene terephthalate (PET) film (manufactured by: KOLON) having a thickness of 12 μm were laminated on one side of an AA8021 aluminum (Al) alloy thin film (manufactured by: SAMA Aluminum) having a thickness of 80 μm by dry lamination using a urethane adhesive to form a base layer. Here, the urethane adhesive was applied so that the adhesive layer had a thickness of 5 μm. Next, molten acid-modified polypropylene (PPa) and polypropylene (PP) were co-extruded on the other side of the aluminum alloy thin film to a thickness of 30 μm each to form a sealant layer having a thickness of 60 μm, thereby manufacturing a pouch film laminate.

[0085] Experimental Example 1: Measurement of tensile strength and elongation of base layer film The base layer film (nylon film / adhesive layer / polyethylene terephthalate film laminate) used in Examples 1 to 4 and Comparative Examples 1 to 4 was cut to a width x length of 15 mm x 80 mm to prepare a sample. Here, the longitudinal direction of the sample was cut to coincide with the TD direction of the pouch film laminate. Then, as shown in Figure 4, the sample was fixed to a UTM device with a grip gap of 30 mm, and the sample was pulled at a pulling speed of 50 mm / min to measure the strength at which breakage occurred as the tensile strength.

[0086] The grip gap at break was divided by the grip gap before stretching (30 mm) and then multiplied by 100 to evaluate the elongation (%).

[0087] The measurement results are shown in Table 2 below.

[0088] Experimental example 2: Fatigue test Each of the pouch film laminates manufactured in Examples 1 to 4 and Comparative Examples 1 to 4 was cut to a size of 266 mm x 240 mm, and then attached to a two-cup molding device equipped with a die and a punch, and the punch was lowered at a pressure of 0.5 MPa and a speed of 50 mm / min to perform drawing. Here, the pouch film laminates of Examples 1 to 4 and Comparative Example 2 were molded to a molding depth of 9.6 mm, and the pouch film laminates of Comparative Examples 1 and 3 were molded to a molding depth of 7.0 mm, which is the limit molding depth at which cracks do not occur.

[0089] Meanwhile, the die conditions for the two-cup molding device are as shown in [Table 1] above.

[0090] Then, the two-cup molded pouch film laminate was cut to a size of 80 mm long x 15 mm wide to prepare a measurement sample. The longitudinal direction was cut to the TD direction of the pouch film laminate. Figure 5 shows the cutting position (box area) of the two-cup molded pouch film laminate. Next, the sample was fixed to the UTM device with a grip gap of 30 mm, and then the lower force was set to 100 N and the higher force was set to 150 N, and the number of times the force was applied until the sample broke was measured. The measurement results are shown in Table 2 below.

[0091] Experimental example 3: Puncture test Each of the pouch film laminates produced in Examples 1 to 4 and Comparative Examples 1 to 4 was cut into a size of 90 mm wide x 100 mm long to prepare a measurement sample. Then, the sample was clamped in the jig of the puncture strength tester shown in Fig. 6, and a load force of 20 N and 22 N was repeatedly applied to the sample with a pin having a diameter of 1.0 mm and a tip curvature of 0.5 mm, and the number of times until a hole was made in the sample was measured.

[0092] The pin was dropped onto the sample while varying the drop load, and the puncture strength of each sample was measured.

[0093] The measurement results are shown in Table 2 below.

[0094] [Table 2]

[0095] From the above [Table 2], it can be seen that in the case of Examples 1 to 4, in which the thickness of the metal layer and the tensile strength and elongation rate in the TD direction of the substrate layer are within the ranges of the present invention, the measurement results of the fatigue test, puncture cycle, and puncture strength are significantly superior to those of Comparative Examples 1 to 3. On the other hand, in the case of Comparative Example 4, in which a substrate layer having a high tensile strength in the TD direction and a low elongation rate is used, it can be seen that the puncture strength and puncture cycle properties are excellent, but the formability is poor, and the fatigue test results are inferior to those of Examples 1 and 2, in which metal layers of the same thickness are used. Therefore, when a battery case is manufactured using the pouch film laminates of Examples 1 to 4, it is possible to obtain the effect of maintaining excellent formability and significantly improving resistance to external stress. [Explanation of symbols]

[0096] 1 Pouch film laminate 10 Base material layer 20 Gas barrier layer 30 Sealant Layer 16a, 16b adhesive layer 100 Battery case 110 Lower case 120 Upper Case 110a, 110b Cup part 130 Bridge

Claims

1. a gas barrier layer, a base layer disposed on one surface of the gas barrier layer, and a sealant layer disposed on the other surface of the gas barrier layer; The thickness of the gas barrier layer is 60 μm or more, The pouch film laminate, wherein the base layer has a tensile strength in the TD direction of 10 kgf / 15 mm to 20 kgf / 15 mm and an elongation rate in the TD direction of 150% to 235%.

2. The pouch film laminate according to claim 1, wherein the pouch film laminate is molded into two cups so as to have a molding depth of 9.6 mm, and then cut into a size of 15 mm x 80 mm to produce a sample. When a force of 100 N and 150 N is repeatedly applied to the sample, the number of times that a force is applied until breakage occurs is 2000 or more.

3. 2. The pouch film laminate according to claim 1, wherein when a sample produced by cutting the pouch film laminate into a size of 90 mm x 100 mm is repeatedly pierced with a pin having a diameter of 1.0 mm at a load of 20 N, the number of times that a force is applied until a hole is made is 250 or more.

4. 2. The pouch film laminate according to claim 1, wherein when a sample produced by cutting the pouch film laminate into a size of 90 mm x 100 mm is repeatedly pierced with a pin having a diameter of 1.0 mm at a load of 22 N, the number of times that a force is applied until a hole is made is 150 or more.

5. The pouch film laminate according to claim 1, wherein the gas barrier layer has a thickness of 60 μm to 100 μm.

6. The pouch film laminate according to claim 1, wherein the base material layer has a tensile strength in a TD direction of 10 kgf / 15 mm to 18 kgf / 15 mm.

7. The pouch film laminate according to claim 1, wherein the elongation percentage in the TD direction of the base material layer is 170% to 235%.

8. The pouch film laminate according to claim 1 , wherein the base layer has a laminated structure of a polyethylene terephthalate film and a nylon film.

9. The thickness of the polyethylene terephthalate film is 5 μm to 20 μm, The pouch film laminate according to claim 8, wherein the nylon film has a thickness of 20 μm to 30 μm.

10. The pouch film laminate of claim 1 , wherein the gas barrier layer comprises an aluminum alloy thin film.

11. The pouch film laminate according to claim 10, wherein the aluminum alloy thin film contains 1.2 wt % to 1.7 wt % iron.

12. The pouch film laminate according to claim 10, wherein the aluminum alloy thin film has a grain size of 10 μm to 13 μm.

13. The pouch film laminate according to claim 1, wherein the sealant layer has a thickness of 60 μm to 100 μm.

14. 10. The pouch film laminate of claim 1, wherein the sealant layer comprises polypropylene, unoriented polypropylene, acid modified polypropylene, polypropylene-butylene-ethylene copolymer, or a combination thereof.

15. A battery case comprising: A battery case comprising the pouch film laminate according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Exterior material for lithium ion battery

    JP2015133327A

  • Laminated body for power storage device outer packaging material

    JP2021190419A

  • Pouch film laminate, pouch-type battery case, and pouch-type secondary battery

    WO2021251736A1